Personality traits and the use of coping strategies in academic oral presentations among Malay ESL learners - Abdul Aziz, Roslina; Ahmad, Badli Esham; Ariffin, Kamisah; Abas, Nadhratunnaim; Kamata, Akiko (Universiti Teknologi Mara Cawangan Pulau Pinang, 2026)
This study examines the relationship between personality traits and coping strategies used by Malay learners during oral presentations. It aims to explore how different personality types may influence communication effectiveness in public speaking contexts. A descriptive–quantitative design was employed, with surveys serving as the main data collection method. Two sets of questionnaires; the MyersBriggs Type Indicator (MBTI) and the Oral Presentation Strategy Inventory (OPSI), were administered to 119 ESL learners enrolled in English courses at a Malaysian public university. The collected data were analysed using SPSS version 29. The findings indicated a predominance of introverted tendencies among participants, accompanied by a practical orientation reflected in their sensing traits. Extroverted learners appeared to perform better than introverted learners; however, both groups adopted comparable coping strategies to manage presentation anxiety. This study offers an in-depth understanding of how personality differences intersect with learners’ communication strategies, extending discussions on individual factors that shape oral performance in ESL contexts. The results provide insights for educators and practitioners on how awareness of personality traits can inform more responsive teaching approaches to enhance learners’ oral presentation skills.